Elevated neuronal nitric oxide synthase expression during ageing and mitochondrial energy production - Lam, Philip Y. (2009)
This study evaluated the effect of ageing on brain mitochondrial function mediated through protein post-translational modifications. Neuronal nitric oxide synthase increased with age and this led to a discreet pattern of nitration of mitochondrial proteins. LC/MS/MS analyses identified the nitrated mitochondrial proteins as succinyl-CoA-transferase and F1-ATPase; the latter was nitrated at Tyr269, suggesting deficient ADP binding to the active site. Activities of succinyl-CoA-transferase, F1-ATPase and cytochrome oxidase decreased with age. The decreased activity of the latter cannot be ascribed to protein modifications and is most likely due to a decreased expression and assembly of complex IV. Mitochondrial protein post-translational modifications were associated with a moderately impaired mitochondrial function, as indicated by the decreased respiratory control ratios as a function of age and by the release of mitochondrial cytochrome c to the cytosol, thus supporting the amplification of apoptotic cascades.